Teachers’ attitude to the use electronic devices in technology lessons, educating pupils with special educational needs - Vaitkevičienė, Asta; Širiakovienė, Asta (Special Education, 2019)
Abilities of pupils with moderate, severe and profound intellectual disabilities are developed in activities. One of such activities is technology lessons with its essential feature – practical orientation. The most important achievements of SEN pupils in the technology subject is formation of practical daily life skills. As provided in The Recommendations on Adaptation of Basic Education General Curricula for Education of Special Needs Pupils with Low and Very Low Intellectual Abilities (2010), technology education consists of such parts as nutrition, textiles, structural materials and electronics. Properly organized electronics lessons prepare special needs pupils for life, form their practical skills, and help them to get familiar with new technologies. It was relevant to find out the attitudes of teachers of special education institutions to the use of electronic devices in the lessons of technology, because previous research did not deal with learning resources of special education institutions, teachers’ attitude to new technologies, and possibilities of using electronic devices.